(untitled) (Research Announcements "Heritage BG", 2025)
The lists of contributors, printed at the end or at the beginning ofrevival books as a token of gratitude from the writer / translator / publisher to those whosefinancial support enabled the publication of a work, contain valuable data on the history and sociology of literature that very often can to be found only in these lists. The analytical systematization of these data in a catalogue of personalities is the basis on which the theoretical understanding of the literary and sociocultural processes during the era is based. References: Dinekov, P. (1937). Sofiya prez XIX vek do Osvobozhdenieto na Bulgariya. Sofia. Kiselkov, V. (1960). Spomoshtestvovatelite na Sofroniy Vrachanski. – V: Izsledvaniya v chest na Marin Drinov. Sofia. Lekov, D. (1982). Literatura – obshtestvo – kultura. Sofia. Nachov, N. (1911). Za nyavgashnite spomoshtnitsi na knigi. – Bulgarska sbirka. Sofia. Nachov, N. (1921). Novobulgarskata kniga i pechatnoto delo u nas v godinite 1806-1878. – SbBAN, kn. 15. Sofia. Nachov, N. (1925). Tsarigrad kato kulturen tsentŭr na bélgarite do 1877 godina. – SbBAN, kn. 19. Sofia. Nachov, N. (1927). Kalofer v minaloto. Sofia. Radev, T. (1956). Obshtestvenite sloeve u spomoshtestvovatelite na nyakoi ot nay-rannite bulgarski staropechatni knigi. – V: Godishnik na Bulgarskiya Bibliografski institut “Elin Pelin”, V, 1955. Sofia. Stoilov, A. P. (1926). Spomoshtnitsi ot Makedoniya na bulgarski pechatni knigi (1814-1877). – V: Izvestiya na Narodniya etnografski muzei v Sofiya, god. VI, kn. I – IV. Sofia. Zhechev, N. (1970). Braila i bulgarskoto kulturno-natsionalno vuzrazhdane. Sofia. Stoyanov, M. (1978). Bukvi i knigi. Sofia.